Computational modelling of amino acid transfer interactions in the placenta. - Sengers, BG; Please, C; Lewis, R (2010)
Amino acid transfer from mother to fetus via the placenta plays a critical role in normal development, and restricted transfer is associated with fetal growth restriction. Placental amino acid transfer involves the interaction of 15 or more transporters and 20 amino acids. This complexity means that knowing which transporters are present is not sufficient to predict how they operate together as a system. Therefore, in order to investigate how placental amino acid transfer occurs as a system, an integrated mathematical/computational modelling framework was developed to represent the simultaneous transport of multiple amino acids. The approach was based on a compartmental model, in which separate maternal, syncytiotrophoblast and fetal volumes were distinguished, and transporters were modelled on the maternal- and fetal-facing membranes of the syncytiotrophoblast using Michaelis-Menten-type kinetics. The model was tested in comparison with placental perfusion experiments studying serine-alanine exchange and found to correspond well. The results demonstrated how the different transporters can work together as an integrated system and allowed their relative importance to be assessed. Placental-fetal serine exchange was found to be most sensitive to basal membrane transporter characteristics, but a range of secondary, less intuitive effects were also revealed. While this work only addressed a relatively simple three amino acid system, it demonstrates the feasibility of the approach and could be extended to incorporate additional experimental parameters. Ultimately, this approach will allow physiological simulations of amino acid transfer. This will enhance our understanding of these complex systems and placental function in health and disease.